Teachers’ Perception and Practices of Learner-Centered Methods in English Language Teaching - Shewangizaw, Gashaw (Graduate School of Universitas Negeri Malang, 2024)
This study explored Ethiopian Technical and Vocational Training Institute English teachers' perceptions and practices of student-centered learning. The interviews and observations results revealed positive teacher attitudes towards student-centered approaches, but classroom practices often remained teacher-centered and reliant on textbooks, disregarding student interests. Challenges included a lack of practical implementation skills, conflicting summative assessments, and the need for continuous formative feedback. Bridging the conceptual-practical divide requires practice-integrated professional development and flexible policies to support autonomy and experience-driven curricula. These findings contribute to understanding contextual realities and refining alignment with evolving workforce demands through ongoing improvement and localized responsiveness.